Tourist Satisfaction Level of Pramuka Island During the COVID-19 Pandemic - Fristi Bellia Annishia; Dio Dwi Saputro (STMIK Indonesia Banda Aceh, 2025)
The Thousand Islands is the only island-based marine tourism destination in Jakarta. As the name suggests, the Thousand Islands consist of thousands of small islands, one of which is Pramuka Island. Pramuka Island is not only a tourist destination but also serves as the administrative center of the Thousand Islands. This makes Pramuka Island play a crucial role in the development of the surrounding islands to enhance tourist satisfaction. The significant decline in tourist visits in 2021 was seen due to the impact of the Covid-19 pandemic. Therefore, it is important to understand the level of visitor satisfaction on Pramuka Island so that tourism destination managers can improve the quality of their services. This study aims to determine the level of visitor satisfaction on Pramuka Island during the Covid-19 pandemic based on a comparison between expectations and reality perceived by visitors regarding product quality and tourism services. This study was conducted in 2022 using a quantitative approach with a sample of 191 respondents. The research instrument was a 19-item questionnaire, which was then analyzed using Microsoft Excel to determine the average value of the gap between expectations and reality perceived by visitors to Pramuka Island. The calculation results showed that the satisfaction level based on product quality was 0.55, categorized as quite satisfied, and service quality was 0.53, categorized as quite satisfied. The purpose of this research is to obtain an overview of visitor satisfaction levels. Therefore, it is hoped that Pramuka Island destination managers will improve service and product quality to increase tourist visits to Pramuka Island.